Ethical Fragmentation and Public Moral Reasoning: Teachers, Religious Pluralism, and Kantian Evaluation in Indonesia - Samsul Ma’arif Mujiharto; Siti Murtiningsih; Sonjoruri Budiani Trisakti (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the ethical architecture of the teaching profession in Indonesia by examining how teacher ethics is governed and evaluated within a context of institutional and religious pluralism. It seeks to explain why teacher ethics has largely functioned as an instrument of professional governance rather than as a framework of public moral reasoning that supports teachers’ moral agency. This study adopts a qualitative normative–philosophical approach, analyzing Indonesian education policy documents—particularly the Regulation of the Minister of Education, Culture, Research, and Technology No. 67 of 2024—and codes of ethics issued by major teacher professional organizations (PGRI, IGI, PERGUNU, and Muhammadiyah). The analysis employs conceptual and argumentative methods, using Kantian ethics as an evaluative framework, while media-reported cases are referenced illustratively to contextualize normative tensions. The study identifies three central findings. First, teacher ethics in Indonesia is primarily framed in the language of compliance, discipline, and procedure, positioning ethics as a mechanism of professional governance. Second, the pluralism of organizational codes of ethics produces ethical fragmentation, whereby similar professional actions may be evaluated differently depending on institutional affiliation and adjudicative authority. Third, this configuration constrains teachers’ moral agency by prioritizing administrative conformity over rational moral justification that is public and universal in character. The findings suggest that addressing ethical fragmentation in the teaching profession requires more than regulatory harmonization or procedural standardization. Instead, there is a need for a shared framework of public moral reasoning that enables plural religious and institutional ethics to be evaluated through consistent and publicly justifiable criteria. Such a framework has implications for education policy, professional ethical governance, and the cultivation of teachers as autonomous moral agents in plural societies. This study contributes to religious studies and professional ethics scholarship by reframing ethical fragmentation not as a technical governance problem but as a problem of public moral justification within plural moral traditions. By employing Kantian ethics as an evaluative lens rather than a prescriptive doctrine, the study offers an original conceptual contribution to debates on religious pluralism, professional ethics, and moral agency in highly regulated educational contexts such as Indonesia.